Do you "like" my photo? Facebook use maintains eating disorder risk. Issue 5 (24th January 2014) - Mabe, Annalise G.; Forney, K. Jean; Keel, Pamela K.
ABSTRACT Objective Social media sites, such as Facebook, merge two factors that influence risk for eating disorders: media and peers. Previous work has identified cross‐sectional and temporal associations between Facebook use and disordered eating. This study sought to replicate and extend these findings using an experimental design. Method In Study 1, 960 women completed self‐report surveys regarding Facebook use and disordered eating. In Study 2, 84 women were randomly assigned to use Facebook or to use an alternate internet site for 20 min. Results More frequent Facebook use was associated with greater disordered eating in a cross‐sectional survey. Facebook use was associated with the maintenance of weight/shape concerns and state anxiety compared to an alternate internet activity. Discussion Facebook use may contribute to disordered eating by maintaining risk for eating pathology. As such, targeting Facebook use may be helpful in intervention and prevention programs. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2014; 47:516–523)